Do credit ratings affect European banks’ equity capital? - BEN HMIDEN, OUSSAMA; BEN ZAIED, YOUNES; BEN CHEIKH, NIDHALEDDINE; BEN LAHOUEL, BECHIR (Bankers, Markets & Investors, 2019)
This study investigates the impact of credit rating changes on banks’ equity capital following the 2008 financial crisis. Using data describing European commercial banks and a robust generalized method of moments estimation method, we find a negative association between equity capital and bank ratings. Investors may perceive a rating downgrade as a signal from rating agencies about a bank’s financial stability. We confirm empirically that riskier European banks are forced to hold higher equity, and that market risk rather than regulatory constraints significantly increases banks’ equity capital.